Arginine substitution by alanine at the P1 position increases the selectivity of CmPI-II, a non-classical Kazal inhibitor - Laritza Rojas; Aymara Cabrera-Muñoz; Dayrom Gil Pradas; Jessica B. González; Maday Alonso-del-Rivero; Yamile González-González (Biochemistry and Biophysics Reports, 2021)
CmPI-II is a Kazal-type tight-binding inhibitor isolated from the Caribbean snail Cenchritis muricatus. This inhibitor has an unusual specificity in the Kazal family, as it can inhibit subtilisin A (SUBTA), elastases and trypsin. An alanine in CmPI-II P1 site could avoid trypsin inhibition while improving/maintaining SUBTA and elastases inhibition. Thus, an alanine mutant of this position (rCmPI-II R12A) was obtained by site-directed mutagenesis. The gene cmpiR12A was expressed in P. pastoris KM71H yeast. The recombinant protein (rCmPI-II R12A) was purified by the combination of two ionic exchange chromatography (1:cationic, 2 anionic) followed by and size exclusion chromatography. The N-terminal sequence obtained as well as the experimental molecular weight allowed verifying the identity of the recombinant protein, while the correct folding was confirmed by CD experiments. rCmPI-II R12A shows a slightly increase in potency against SUBTA and elastases. The alanine substitution at P1 site on CmPI-II abolishes the trypsin inhibition, confirming the relevance of an arginine residue at P1 site in CmPI-II for trypsin inhibition and leading to a molecule with more potentialities in biomedicine.